Exploring the pathogenesis of MAFLD from an immunological perspective: from the perspective of the cGAS/STING/NF-κB signaling pathway - Tian, Ruiyuan; Li, Yong (Frontiers in Immunology, 2025)
Metabolic-Associated Fatty Liver Disease (MAFLD) is the most common cause of chronic liver disease and also a major contributor to liver disease-related complications and mortality. It is closely associated with cardiovascular disease (CVD), stroke, type 2 diabetes mellitus (T2DM), chronic kidney disease (CKD), and non-liver tumors, and has become a significant global public health issue. In recent years, studies have respectively revealed the relationships between the cGAS/STING and STING/NF-κB signaling pathways and MAFLD. Although, in addition to cyclic GMP-AMP synthase (cGAS), various other DNA sensors can also recognize DNA molecules and activate stimulator of interferon genes (STING), their localization response capability and hepatocyte targeting are relatively weak, and most of them only function in specific cell types or physiological states. As a key innate immune mediator, cGAS is the core molecule that activates the classical STING pathway. Therefore, the cGAS/STING/NF-κB signaling pathway may form an important pathological chain of “DNA stress - inflammation - metabolic abnormality” in MAFLD. Consequently, it is necessary to explore the mechanism of action and research progress of the cGAS/STING/NF-κB signaling pathway in MAFLD, which provides new insights for the mechanism research and treatment of MAFLD.